Prolonged transfer of feces from the lean mice modulates gut microbiota in obese mice. Issue 1 (December 2016) - Kulecka, Maria; Paziewska, Agnieszka; Zeber-Lubecka, Natalia; Ambrozkiewicz, Filip; Kopczynski, Michal; Kuklinska, Urszula; Pysniak, Kazimiera; Gajewska, Marta; Mikula, Michal; Ostrowski, Jerzy
Abstract Background Transplanting a fecal sample from lean, healthy donors to obese recipients has been shown to improve metabolic syndrome symptoms. We therefore examined the gut microbiota in mice after administering a long-term, high-fat diet (HFD) supplemented with feces from lean mice through the fecal-oral route. Methods C57BL6/W mice were allowed to adapt to a non-specific pathogen free (SFP) environment for 2 weeks before being divided into three groups of 16 animals. Animals were fed for 28 weeks with a normal diet (ND), HFD or HFD supplemented with feces from ND-fed mice (HFDS). The composition of colonizing bacteria was evaluated in droppings collected under SPF conditions at the beginning of the study and at 12 and 28 weeks using an 16S Metagenomics Kit on Ion PGM sequencer. Results HFD and HFDS-fed mice attained (p  < 0.05) greater body weights by weeks 6 and 5, respectively. HFDS-fed mice gained more weight than HFD-fed mice by week 25. Both species diversity and richness indices increased with time in HFDS mice only. Conclusions Prolonged HFD-fed mice supplementation with feces from lean mice altered bacteria species diversity and richness, accelerated the onset of obesity, and caused increased weight gain in the later weeks of the HFD regimen.